The Impact of Traditional Classroom Based Teaching in Comparison to Online Teaching on the Academics and Attendance of Male and Female Students - Butt, Hira; Khan, Nauman; Amjad, Khadija; Hafeez, Fatima; Tahir, Fizza; Sahaf, Hamza Ahmad (Journal of Gandhara Medical and Dental Science, 2021)
OBJECTIVES: To compare the impact of traditional classroom-based teaching versus online teaching on the academics and attendance of male as compared to female students METHODOLOGY: A study was conducted on 51 third year BDS students, College of Dentistry, Sharif Medical and Dental College, Lahore. An aggregate of the scores based on weightage assigned to each test for all the assessments conducted in the regular session and online session was formulated. The attendance record of the months taught in both the sessions was also taken as percentages. Fisher Exact test was used to find the statistical association between the level of academic performance as well as attendance in the regular session and online session with gender of the students. Man Whitney U test was used to find the statistical difference in the scores of assessments in the regular as well as online session of male and female students. RESULTS: There was a significant association between gender and academic performance in the online session (p=0.002). Gender and academic performance of students during the traditional classroom-based teaching session had a significant association (p=0.001). The attendance of male and female students was found to be significantly associated with the online teaching system (p=0.009). CONCLUSION: It was observed that females had an overall better academic performance in the online teaching as well as traditional classroom-based teaching system. A similar trend was observed in attendance also, where the females had better attendance record in online and traditional classroom-based teaching set up.